Perceptions of Knowledge and Attitudes of the Community in Making Decisions on Purchasing Halal Products - Meliana Meliana; Ahmad Fauzul Hakim Hasibuan; Dinda Sandia; Putri Nadifa Afrila (LPPM UIKA Bogor, 2023)
This research is a research using descriptive qualitative method. Data collection techniques were carried out by distributing questionnaires and interviews. This research was conducted to find out how public perceptions are in making decisions on purchasing halal products. The research location was conducted in the city of Lhokseumawe. The population in this study is the people in Lhokseumawe City, while the number of successful samples is 117 responses using purposive sampling method. From the number of questionnaires distributed, there were 130. The criteria used as a benchmark in this study were respondents from Lhokseumawe society, adolescents and adults. The results of this study showed that the percentage of people's understanding of the consumption of halal products was higher compared to people who lacked understanding and did not understand, showing a small percentage